DEVELOPMENT OF FLIP PDF CORPORATE EDITION FLIP BASED E-MODULE TEACHING MATERIALS ON TRANSACTION DOCUMENT MANAGEMENT MATERIALS IN CLASS X VOCATIONAL SCHOOLS - Trishe Silinia Arafah; Yopi Nisa Febianti (Cirebon International Conference on Education and Economics Proceeding, 2024)
This research aims to analyze the e-module design, analyze the feasibility of the e-module content, and determine expert validation tests for the e-module. E-module teaching materials developed using flip pdf corporate edition on transaction document management material in class X SMK. This research includes research and development (R&D) which uses 3D models, namely Define, Design and Development. There are 3 expert validators to assess the product being developed from the e-module design aspect, the suitability aspect of the e-module content, and the e-module teaching material aspect. The validity test results for the e-module design aspect were 88.33% in the very feasible category, then the feasibility aspect of the e-module content was 85.41 in the very feasible category, and the e-module teaching materials aspect was 75% in the very feasible category. very worthy category. The total results obtained from expert validation of e-module teaching materials were 82.91%, included in the very suitable category.